Spatiotemporal diet shifting in a neotropical fish species: The role of riparian vegetation and seasonal inundation - Mateus, Lucia; Rodrigues Costa, Rosa Maria; Penha, Jerry (Frontiers in Environmental Science, 2022)
Aquatic organisms that consume resources from riparian vegetation or floodplain forests act as trophic links between aquatic and terrestrial ecosystems. For instance, the pacu Piaractus mesopotamicus (Holmberg 1887), which is a migratory fish species, can play an important role in this interaction on Neotropical floodplains. We compared the stomach content of individuals from this species between two different parts of a large river floodplain during contrasting hydrological seasons to quantify the spatiotemporal contribution of allochthonous and autochthonous resources in their diet. Moreover, we performed a bipartite network approach to evaluate the sensitivity of these populations to a simulated loss of food resources through the potential deforestation of riparian vegetation. We found that in the upper catchment, individuals fed mainly on allochthonous items, but their identity depended on the season: fruits were the most abundant resource during the wet season, whereas leaves were more consumed during the dry season. In the lower catchment, the contribution of allochthonous resources was slightly lower in the dry season than in the wet season, when the pacu was able to explore the floodplain. Finally, the results from our consumer-resource network model indicated that this system is vulnerable to riparian deforestation since P. mesopotamicus is highly dependent on input from the riparian vegetation items to your its feed.